Discursive Processes of Intergenerational Transmission of Recent History (Re)making Our Past - Achugar, Mariana; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
Debates about how to remember politically contested or painful pasts exist throughout the world. As with the case of the Holocaust in Europe and Apartheid in South Africa, South American countries are struggling with the legacy of state terrorism left by the 1970s dictatorships. Coming to terms with the past entails understanding the role different social actors played in those events as well as what those event mean for us today. Young people in these situations have to learn about painful historical events over which there is no national consensus. This book explores discursive processes of intergenerational transmission of recent history through the case of the Uruguayan dictatorship. The main themes of the book are the discursive construction of social memory and intergenerational transmission of contested pasts through recontextualization, resemiotization and intertextuality.
Keywords: Ethnology-Latin America; Sociolinguistics; Ethnicity; America-History.; Linguistics, general; Communication Studies